Design, synthesis and pharmacological evaluation of CVIB, a codrug of carvacrol and ibuprofen as a novel anti-inflammatory agent - de Oliveira Pedrosa Rolim, Michelle; de Almeida, Anderson Rodrigues; da Rocha Pitta, Maira Galdino; de Melo Rêgo, Moacyr Jesus Barreto; Quintans-Júnior, Lucindo José; de Souza Siqueira Quintans, Jullyana; Heimfarth, Luana; Scotti, Luciana; Scotti, Marcus Tullius; da Cruz, Ryldene Marques Duarte; de Almeida, Reinaldo Nóbrega; da Silva, Teresinha Gonçalves; et al. (Elsevier, 2019)
The search for new drugs with anti-inflammatory properties remains a challenge for modern medicine. Among the various strategies for drug discovery, deriving new chemical entities from known bioactive natural and/or synthetic compounds remains a promising approach. Here, we designed and synthesized CVIB, a codrug developed by association of carvacrol (a phenolic monoterpene) with ibuprofen (a non-steroidal anti-inflammatory drug). In silico pharmacokinetic and physicochemical properties evaluation indicated low aqueous solubility (LogP ≥5.0). Nevertheless, the hybrid presented excellent oral bioavailability, gastrointestinal tract absorption, and low toxicity. CVIB did not present cytotoxicity in peripheral blood mononuclear cells (PBMCs), and promoted a significant reduction in IL-2, IL-10, IL-17, and IFN-γ cytokine levels in vitro. The LD50 was estimated to be approximately 5000 mg/kg. CVIB was stable and detectable in human plasma after 24 h. In vivo anti-inflammatory evaluations revealed that CVIB at 10 and 50 mg/kg i.p. caused a significant decrease in total leukocyte count (p < 0.01) and provoked a significant reduction in IL-1β (p < 0.01). CVIB at 10 mg/kg i.p. efficiently decreased inflammatory parameters better than the physical mixture (carvacrol + ibuprofen 10 mg/kg i.p.). The results suggest that the codrug approach is a good option for drug design and development, creating the possibility of combining NSAIDs with natural products in order to obtain new hybrid drugs may be useful for treatment of inflammatory diseases.
Keywords: Anti-inflammatory activity; Carvacrol; Cytokines; Hybrid compound; Ibuprofen